2014
DOI: 10.1007/s10532-014-9695-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the catabolic pathway for a phenylcoumaran-type lignin-derived biaryl in Sphingobium sp. strain SYK-6

Abstract: Sphingobium sp. strain SYK-6 is capable of degrading various lignin-derived biaryls. We determined the catabolic pathway of a phenylcoumaran-type compound, dehydrodiconiferyl alcohol (DCA) in SYK-6, and identified some of the DCA catabolism genes. In SYK-6 cells, the alcohol group of DCA was oxidized to the carboxyl group, first at the B-ring side chain and then at the A-ring side chain. The resultant metabolite was degraded to 5-formylferulate and vanillin through the decarboxylation and the Cα-Cβ cleavage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 24 publications
3
50
0
Order By: Relevance
“…We later found a similar catabolic route for DCA in SYK-6, and provided a detailed characterization ( Fig. 1) (33). In SYK-6 cells, the alcohol group of the B-ring side chain of DCA was first oxidized to the carboxyl group to generate 3-(2-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl) acrylic acid (DCA-C) via an aldehyde derivative, 3-(2-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl) acrylaldehyde (DCA-L).…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…We later found a similar catabolic route for DCA in SYK-6, and provided a detailed characterization ( Fig. 1) (33). In SYK-6 cells, the alcohol group of the B-ring side chain of DCA was first oxidized to the carboxyl group to generate 3-(2-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl) acrylic acid (DCA-C) via an aldehyde derivative, 3-(2-(4-hydroxy-3-methoxyphenyl)-3-(hydroxymethyl)-7-methoxy-2,3-dihydrobenzofuran-5-yl) acrylaldehyde (DCA-L).…”
mentioning
confidence: 61%
“…In addition, since the activities of extracts of the SYK-6 cells grown with or without DCA were almost the same, the genes encoding DCA-converting enzymes seem to be constitutively expressed. In our previous study, we suggested the involvement of multiple quinohemoprotein ADHs and aryl ADHs in the DCA oxidation (33). However, since quinohemoprotein ADHs are usually localized in the membrane or periplasm (42), aryl ADHs appear to play an important role in the oxidation of DCA.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations